KREATIVLIK XUSUSIYATLARINI GENETIK OMILLARGA BOG‘LIQLIGINI О‘RGANISHNING EMPIRIK ASOSLARI - Odiljonova, А.А. (SCIENCE and SOCIETY, 2024)
It is important to study the problem of creativity psychologically, to pау attention to genetic factors in the formation of creativity in а person. In the article, the scientific researches of many psychogenetic researchers who studied the problem of influence of genotype on the development of creativity are mentioned. Issues of the presence of an innate biological factor in creativity, genetically determined typological characteristics of creativity and nervous system characteristics are highlighted.
Keywords: phenomenon of creativity; genetic factors; divergent thinking; features of the nervous system; extroversion; introversion